Fibrinogen-Like Protein 1 Serves as an Anti-Inflammatory Agent for Collagen-Induced Arthritis Therapy in Mice - Lin, Wen-Wei; Ho, Kai-Wen; Su, Hsiang-Han; Fang, Tien-Fang; Tzou, Shey-Cherng; Chen, I-Ju; Lu, Yun-Chi; Chang, Mu-Shen; Tsai, Yun-Chen; Liu, En-Shuo; Su, Yu-Cheng; Wang, Yen-Tseng; et al. (Frontiers in Immunology, 2021)
Fibrinogen-like protein 1 (FGL1) was recently identified as a major ligand of lymphocyte-activation gene-3 (LAG-3) on activated T cells and serves as an immune suppressive molecule for regulation of immune homeostasis. However, whether FGL1 has therapeutic potential for use in the T cell-induced the autoimmune disease, rheumatoid arthritis (RA), is still unknown. Here, we attempted to evaluate the effect of FGL1 protein on arthritis progression. We also evaluated potential adverse events in a collagen-induced arthritis (CIA) mouse model. We first confirmed that soluble Fgl1 protein could specifically bind to surface Lag-3 receptor on 3T3-Lag-3 cells and further inhibit interleukin (IL-2) and interferon gamma (IFNγ) secretion from activated primary mouse T cells by 95% and 43%, respectively. Intraperitoneal administration of Fgl1 protein significantly decreased the inflammatory cytokine level (i.e., IL-1β and IL-6) in local paw tissue, and prevented joint inflammation, cellular infiltration, bone deformation and attenuated collagen-induced arthritis progression in vivo. We further demonstrated that exogenous Fgl1 does not cause obvious adverse events during treatment by monitoring body weight and liver weight, and assessing the morphology of several organs (i.e., heart, liver, spleen, lung and kidney) by pathological studies. We expect that Fgl1 protein may be suitable to serve as a potential therapeutic agent for treatment of RA or even other types of T cell-induced autoimmune or inflammatory diseases in the future.